Transcriptomic analysis of succulent stem development of Chinese kale (Brassica oleracea var. alboglabra Bailey) and its synthetic allotetraploid via RNA sequencing - Zheng, Wen; Shi, Jiang; Zhu, Zhi-Yu; Jin, Ping; Chen, Jia-Hong; Zhang, Liang; Zhang, E.; Lin, Tao; Zhu, Zhu-Jun; Zang, Yun-Xiang; Wu, Jian-Guo (Frontiers in Plant Science, 2022)
Chinese kale (Brassica oleracea var. alboglabra Bailey, CC) is a succulent stem vegetable in the Brassica family. Its allotetraploid (AACC) vegetable germplasm, which was synthesized via distant hybridization with the colloquially named ‘yellow turnip’ (B. rapa L. ssp. rapifera Matzg., AA), has a swelling stem similar to CC. To address the molecular mechanism of stem development for CC and AACC, RNA sequencing (RNA-seq) was used to investigate transcriptional regulation of their stem development at three key stages including 28 days, 42 days and the bolting stage (BS) after sowing. As a result, 32,642, 32,665, 33,816, 32,147, 32,293 and 32,275 genes were identified in six corresponding cDNA libraries. Among them, 25,459 genes were co-expressed, while 7,183, 7,206, 8,357, 6,688, 6,834 and 6,814 genes were specifically expressed. Additionally, a total of 29,222 differentially expressed genes (DEGs) were found for functional enrichment as well as many genes involved in plant hormones including gibberellin (GA), abscisic acid (ABA), cytokinin (CTK) and auxin (AUX). Based on gene expression consistency between CC and AACC, the gene families including DELLA, GID, PYR/PYL, PP2C, A-ARR and AUX/IAA might be related to stem development. Among these, eight genes including Bo00834s040, Bo5g093140, Bo6g086770, Bo9g070200, Bo7g116570, Bo3g054410, Bo7g093470 and Bo5g136600 may play important roles in stem development based on their remarkable expression levels as confirmed by qRT-PCR. These findings provide a new theoretical basis for understanding the molecular mechanism of stem development in Brassica vegetable stem breeding.